The Role Of Land Owner Farmers In Sustainable Food Agricultural Land Protection - Hardimen; Fauzia Zainin; Darlisma (LPPM Universitas Ekasakti Padang, 2024)
Sustainable agricultural development is faced with competition for the use of agricultural land and the preservation of the function of land resources and the environment. Agricultural land conversion is a sectoral issue, a regional issue and a national issue in providing food for the community. The conversion of agricultural land and the need to protect food agricultural land has so far not become a major issue in regional development planning. This research aims to see to what extent farmers who own land play a role in protecting sustainable food agricultural land. This research uses primary data sources, secondary data and tertiary data. Primary data was obtained directly through interviews with sources from the Department/Agency that handles LP2B. The results of the research show that the standard area of ​​rice fields in West Pasaman Regency in 2016 - 2022 saw a reduction in the area of ​​rice fields by 3,948 Ha. This reduction in rice fields is due to the conversion of agricultural land into oil palm plantations, settlements and housing as well as due to damage to irrigation dams and sub-optimal irrigation channels and others. This research also found the supporting capacity for land and food protection in the form of local wisdom in several Nagari-nagari such as in Kinali District, Desa Baru and Kenagarian Talu, this is a form of concern in keeping rice fields eternal, and of course the Regional Government of West Pasaman Regency must be more proactive in encouraging and developing the role of farmers who own land which is based on local wisdom in maintaining and caring for permanent rice fields. eternal community as sustainable agricultural land.